Patients' Experiences of a National Patient Portal and Its Usability: Cross-Sectional Survey Study - Saija Simola; Iiris Hörhammer; Yuhui Xu; Annika Bärkås; Asbjørn Johansen Fagerlund; Josefin Hagström; Mari Holmroos; Maria Hägglund; Monika Alise Johansen; Bridget Kane; Anna Kharko; Isabella Scandurra; et al. (JMIR Publications, 2023)
BackgroundPatient portals not only provide patients with access to electronic health records (EHRs) and other digital health services, such as prescription renewals, but they can also improve patients' self-management, engagement with health care professionals (HCPs), and care processes. However, these benefits depend on patients' willingness to use patient portals and, ultimately, their experiences with the usefulness and ease of use of the portals. ObjectiveThis study aimed to investigate the perceived usability of a national patient portal and the relationship of patients' very positive and very negative experiences with perceived usability. The study was aimed to be the first step in developing an approach for benchmarking the usability of patient portals in different countries. MethodsData were collected through a web-based survey of the My Kanta patient portal's logged-in patient users in Finland from January 24, 2022, to February 14, 2022. Respondents were asked to rate the usability of the patient portal, and the ratings were used to calculate approximations of the System Usability Scale (SUS) score. Open-ended questions asked the patients about their positive and negative experiences with the patient portal. The statistical analysis included multivariate regression, and the experience narratives were analyzed using inductive content analysis. ResultsOf the 1,262,708 logged-in patient users, 4719 responded to the survey, giving a response rate of 0.37%. The patient portal's usability was rated as good, with a mean SUS score of 74.3 (SD 14.0). Reporting a very positive experience with the portal was positively associated with perceived usability (β=.51; P<.001), whereas reporting a very negative experience was negatively associated with perceived usability (β=−1.28; P<.001). These variables explained 23% of the variation in perceived usability. The information provided and a lack of information were the most common positive and negative experiences. Furthermore, specific functionalities, such as prescription renewal and the ease of using the patient portal, were often mentioned as very positive experiences. The patients also mentioned negative emotions, such as anger and frustration, as part of their very negative experiences. ConclusionsThe study offers empirical evidence about the significant role of individual experiences when patients are evaluating the usability of patient portals. The results suggest that positive and negative experiences provide relevant information that can be used for improving the patient portal's usability. Usability should be improved so that patients receive information efficiently, easily, and quickly. Respondents would also appreciate interactive features in the patient portal.